Obesity and Breast Cancer: The Roles of Peroxisome Proliferator-Activated Receptor-γ and Plasminogen Activator Inhibitor-1 - Jennifer C. Carter; Frank C. Church (PPAR Research)
Breast cancer is the most prominent cancer among females in the United States. There are a number of risk factors associated with development of breast cancer, including consumption of a high-fat diet and obesity. Plasminogen activator inhibitor-1 (PAI-1) is a cytokine upregulated in obesity whose expression is correlated with a poor prognosis in breast cancer. As a key mediator of adipogenesis and regulator of adipokine production, peroxisome proliferator-activated receptor-γ (PPAR-γ) is involved in PAI-1 expression from adipose tissue. We summarize the current knowledge linking PPAR-γ and PAI-1 expression to high-fat diet and obesity in the risk of breast cancer.